2016
DOI: 10.1089/lap.2015.0551
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stump Pressure in Three Types of Appendectomy: Harmonic Scalpel, LigaSure, and Conventional Technique

Abstract: Appendectomies carried out with LigaSure and Harmonic Scalpel are as safe as appendectomies carried out with the conventional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…A similar study to ours but assessing safety was conducted by Yavuz et al and it proved that ligation and stump closure with ultrasonic dissector was as safe as it was with silk sutures [12]. However, this study did not produce any measurable outcomes unlike our study.…”
Section: Discussionsupporting
confidence: 66%
“…A similar study to ours but assessing safety was conducted by Yavuz et al and it proved that ligation and stump closure with ultrasonic dissector was as safe as it was with silk sutures [12]. However, this study did not produce any measurable outcomes unlike our study.…”
Section: Discussionsupporting
confidence: 66%
“…Campagnacci et al [33] found no difference in the duration for colorectal surgery between the two devices, but there was less bleeding with LS. No statistical difference was also detected by Yavuz et al [34] in a randomised trial with 24 cases of laparoscopic appendicectomy. Rimonda et al [35] analyzed results from 140 patients (31 right hemicolectomies, 69 left hemicolectomies, and 40 anterior resections of rectum): they concluded that LigaSure and Harmonic are both useful and safe instruments for laparoscopic colorectal surgery with no significant difference in terms of intraoperative/postoperative morbidity and operative time.…”
Section: Discussionmentioning
confidence: 59%
“…Yavuz et al studied 24 specimens of subtotal colectomy or right hemicolectomy and used a harmonic scalpel, conventional technique, and LigaSure for appendectomy. All three techniques were found to be equally safe [ 18 ].…”
Section: Discussionmentioning
confidence: 99%